'Testing it in the real world': Using action research to apply a conceptual framework to social care planning. Issue 2 (June 2021) - Collings, Susan; Dew, Angela; Dowse, Leanne
This paper outlines an action research methodology used to create a practice-informed resource for social care in Australia. Practitioners and researchers worked together to develop, test and refine a process to engage people with cognitive disability and complex support needs in person-centred planning. The planning approach, which calls for planners to reflect on their own skills and attitudes as well as the unique needs of an individual, has helped to improve practice in a number of fields and locations in Australia. The process marks a substantive practice shift towards recognition of planning as fundamentally relational in nature. This paper reflects on the process of action research which we describe as similarly relational and potentially transformative of the relations between researchers and practitioners. Working within a knowledge translation paradigm we show how reflexivity within the researcher/practitioner relationship in action research calls for a substantive shift in perspective by researchers to effectively work within the complex contexts of practitioners themselves. In taking this opportunity in our research practice, we identify the potential for a fundamentally different praxis to emerge, one more deeply grounded in the conceptual, political and practical relations between researchers, practitioners and those whose lives they seek to enhance.